A DECISION SUPPORT SYSTEM FOR THE IDENTIFICATION OF EMOTIONAL INTELLIGENCE (FUDMA JOURNAL OF SCIENCES, 2024)
Emotional intelligence is the relationships that directly impact how people relate to themselves and to others within a socio-cultural environment. A person who possesses emotional intelligence is able to communicate effectively while controlling and understanding other individual’s emotional inclinations. Individuals desire to express their state of mind, worries, traumas, and obstacles in life as well as get answers and help for their problems. However, they desire security and protection for the feelings, anxieties, trauma, and life obstacles they express. Therefore, individuals require a support structure where they can discuss their problems and seek potential answers while knowing that their identities would be kept private. A “Decision Support System” (DSS) for emotional intelligence is a electronic program that supports decisions, judgments, courses of action, and the proficiency of deploying artificial intelligence (AI) to regulate both your own and those around you emotionally. In this study we use AI to help in decision making to create confidential space between user and app. The technology uses are JavaScript, HTML, openAI, Replicate, PINECONE, CSS, PHP and MySQL. This research shows how technology has the ability to improve emotional intelligence using decision support system in individual’s daily lives.
Keywords: Artificial Intelligence; Emotional intelligence; Communication; Decision Support System; Organization